Penerapan Pendidikan Karakter Dalam Pembelajaran Ppkn Di Era 5.0 Kelas V SDN Gempollegundi - Zulia Rahma Dela; Emy Yunita Rahma Pratiwi (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
The purpose of this research is to apply the character education model in era 5.0, to find out the obstacles faced, and the efforts that can be made in character education for grade V-A students at SDN Gempollegundi. This research is a descriptive qualitative research with case study method. The reseatch subjects were the prinsipal, class V-A teacher, V-A student and gardener. Sources of research data, researchers obtained from observations, interviews, and documentation. Data collection techniques through interview techniques, observation, and documentation. The validity of the data in this study is technical triangulation and peer discussion. Data analysis was carried out through the process of data reduction, data presentation and drawing conclusions. The results showed that (1)The application of character education in civics learning in class V-A era 5.0 in K13 learning was carried out by the teacher by giving real examples to students,appreciating differences, instilling disciplined attitudes, disposing of garbage according to its type and instilling social attitudes. (2) The results of the application of character education in PPKn learning in the classroom can be seen from teaching and learning activities in class showing several attitudes, among others, mutual respect, collecting assignments on time, leaving class asking for permission, not being noisy in class, and independent learning not depending on other people. other. (3) Barriers and solutions for implementing character education at SDN Gempollegundi. The obstacles are the lack of cooperation between the school and parents, students often ignore politeness, teachers do not respond to programs made by school principals who are still concerned with their personal interests. The solution to this obstacle is establishing communication between the school and parents, reminding each other between students and increasing cooperation between the teacher councils.